Association of Human Leukocyte Antigens Class I & II with Graves’ Disease in Iranian Population - Zahra Mehraji (Iranian Journal of Immunology, 2017)
Background: Graves’ disease (GD), a highly rampant autoimmune disorder of the thyroid gland, is responsible for 60-80% of the clinical cases of hyperthyroidism. Over the past decades, genetic association studies have identified several GD susceptibility loci in CTLA-4, TSHR and major histocompatibility complex regions. The information on the association between the human leukocyte antigens (HLA) and GD among Iranians is scarce. Objective: To identify HLA polymorphisms that might confer susceptibility or protect against GD. Methods: Eighty unrelated patients with a confirmed diagnosis of GD were included in the case group. The control group consisted of 180 unrelated healthy individuals with normal thyroid function tests. The polymerase chain reaction with sequence specific primers (PCR-SSP) method was used for HLA typing. Results: Frequencies of HLA-A*68 (15.6% vs. 4.2%, p=0.004) and B*08 (8.8% vs. 2.5, p=0.030) were significantly higher in patients with GD compared with healthy controls. No patients with GD had HLA-A*33, whereas it was found in 7.0% of the controls (p=0.011). HLA-DQB1*0201 was significantly less frequent among patients with GD (15.6% vs. 26.8%, p=0.040). Additionally, patients with GD were significantly less bound to have HLA-DQA1*0201 (6.2% vs. 15.1%, p=0.045). Concerning allelic distributions, no noticeable difference was found between GD patients with and without Graves’ ophthalmopathy (p>0.05 in all cases). Conclusion: In the Iranian population, HLA-A*68 and -B*08 confer susceptibility to GD, whereas HLA-A*33, -DQB1*0201, and -DQA1*0201 appear to have protective roles.